Characterization of patients with stroke in an emergency service from Santiago de Cuba - Dayami Lescay Balanquet; Gerardo Téllez Gamayo; Marlene Fong Osejo; Fátima Flores Bolívar; Eulises Guerra Cepena (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: The stroke is the neurological damage that happens when one of the brain blood vessels is obstructed by a clot (embolism or clot) or it breaks (hemorrhages), which doesn't allow the brain blood flow.  Objective: To characterize the patients with stroke assisted in the Emergencies Service of   Dr. Joaquín Castillo Duany Teaching Clinical Surgical Hospital in Santiago de Cuba.  Methods: A descriptive and cross-sectional study of 122 patients with stroke assisted in the mentioned Service from October, 2016 to the same month in 2017 was carried out. Demographic variables of interest related to the disease were taken into account and the percentage as summary measure was used.  Results: The female sex (58.2 %) and 61-70 age group prevailed in the series.  It was demonstrated that 26.2 % of those affected stayed more than 6 hours in the Emergencies Service and it was found an association of this disease with hypertension, diabetes mellitus, ischemic heart disease, nicotine addiction,  alcoholism and  hyperlipemia; equally, the inadequate use of the pharmacological treatment and  the mechanic artificial ventilation  caused a high lethality rate.  Conclusions: In spite of the studies carried out in this same institution, it is important to continue deepening in the appropriate control and follow up of these accidents, as well as to develop strategies that allow training and preparation of the medical  and paramedic staff of that hospital.